2012
DOI: 10.1108/17581181211273110
|View full text |Cite
|
Sign up to set email alerts
|

What makes a good university lecturer? Students’ perceptions of teaching excellence

Abstract: PurposeThe purpose of this paper is to argue that, in order to achieve teaching excellence, student engagement in dialogue on this important matter is needed. Students’ conceptualisations of good teaching are fundamental when building an understanding of what this is and how it can be developed.Design/methodology/approachThis paper reports on findings of a qualitative study of undergraduate students’ perceptions of a good university lecturer. The paper draws on the secondary dataset collected by four subject c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 15 publications
3
51
0
3
Order By: Relevance
“…Community, openness to others, learner interaction, reflection, inclusive practices and the knowledge and personal experiences each learner brings with them inform the pedagogic approaches as illustrated in our sketches. In our view this conceptualisation of 'ordinary cosmopolitanism' may also support our professional learning (Wood and Su 2014) and our endeavours in achieving 'teaching excellence' in our practice (Su and Wood 2012).…”
Section: Resultsmentioning
confidence: 77%
“…Community, openness to others, learner interaction, reflection, inclusive practices and the knowledge and personal experiences each learner brings with them inform the pedagogic approaches as illustrated in our sketches. In our view this conceptualisation of 'ordinary cosmopolitanism' may also support our professional learning (Wood and Su 2014) and our endeavours in achieving 'teaching excellence' in our practice (Su and Wood 2012).…”
Section: Resultsmentioning
confidence: 77%
“…While there is plenty of research that has problematised student evaluations of teaching (SET) (Alhija & Fresko, 2009;Spooren, Brockx, & Mortelmans, 2013;Su & Wood, 2012), they can reveal the perceptions Ramsden spoke about in 1979. In research-intensive universities, too many students feel the staff are distant figures who are only available during lectures and office hours, and that departments lack a sense of community (Kandiko & Mawer, 2013).…”
Section: When Staff and Students View Each Other As Peers Widely Helmentioning
confidence: 99%
“…This is also reflected in how the relationships between teachers, students and the T & L orient themselves (e.g. Tubbs 2005;Su and Wood 2012). Previous research has identified traits of teaching excellence (e.g.…”
Section: Learning About Teaching and Learning In Higher Education: Comentioning
confidence: 99%